Use of comics in the promotion of school children’s health: a scoping review - Soares, Amanda; Santos, Ana Beatriz Macêdo Venâncio dos; Vieira, Tainelly Souza de; Xavier, Bárbara Letícia de Queiroz; Lucas, Ricardo Jorge de Lucena; Oliveira, Ângelo Giuseppe Roncalli da Costa (Frontiers in Communication, 2024)
This scoping review provides an analysis of the available experiences on the use of comics to promote the health of school children. It was registered in the Open Science Framework (OSF) under DOI: doi.org/10.17605/OSF.IO/Z5VX6. Seventeen studies were used, including articles, theses and dissertations. The results present the main characteristics of the studies such as year; country; sample characteristics; study design; description of actions and population/sample. The target population of each selected study was children younger than 10 years. The sample number of the studies ranged between 47 and 881 children. Fifteen studies developed the interventions in schools. 44.4% of the selected studies were published between 2011 and 2020, and the continents with the highest number of publications were South America and North America, with 33.3% each. Regarding the type of study, 55.6% used the non-randomized experimental method and 35.3% had themes related to specific diseases. The experiences that were considered successful were conditioned to the organizational structure of the use of comic books and how they were offered to school children.